Respostas

2014-07-14T12:05:44-03:00
x² + 2x +a = x² + 8x 
x²-x²+2x+a=8x (corta-se o x²)
a=8x-2x
a=6x
x² + 2x +4 = x² + 8x

2x-8x=-4(-1)
6x=4
x=4/6(:2/2)
x=2/3



















2014-07-14T13:02:23-03:00
x² + 2x +a = x² + 8x ???? Ajudaaaa por favor !!!
corrigindo  a = 4
x² + 2x + 4 = x² + 8x---------------gulalar a ZERO
x² + 2x + 4 - x² - 8x = 0
X² - X² + 2X - 8X + 4 = 0
      0           -6x + 4 = 0
                   
 -6x + 4 = 0
-6x + - 4
x = - 4/-6
x = + 4/6 (divide ambos por 2)
x = 2/3

FAZENDO A VERIFICAÇÃO

X² + 2X + 4 = X² + 8X -------------para     x = 2/3

(2/3)² +2(2/3) + 4 = (2/3)² + 8(2/3)
2²/3²  + 2.2/3 + 4 = 2²/3³   + 8.2/3
4/9     + 4/3   + 4 = 4/9 + 16/3

4           4                4        16
----  + ------   + 4 = ----- + ------
9          3                 9          3


 4 + 12       + 36       4    +  48
---------------------=  -------------
                9                   9

           52                    52
---------------------  = ------------
            9                      9     então está correto